(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The present study is intended to discuss the diffuse incidental unconstitutionality as a guarantee of the right to citizenship. In countries where constitutional legislation is written and conservative, makes specific mechanisms necessary so that laws can be changed or repealed. The Constitution Brazilian Federal Government adopted the control of concentrated or diffuse constituciolity. Every time, that any act or omission violates constitutional precepts, there is the unconstitutionality exercised through the controls. In this sense, in the case of diffuse control, it may be exercised by any citizen in the individual legal proceedings. It is concluded that every citizen will be able to exercise control of constitutionality, requiring the unconstitutionality of an act, omission or law that contrary to precepts constitutional to maintain fundamental guarantees and exercise their rights. For construction of this work, were used, books, periodicals, scientific articles from renowned websites and other materials.